(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article analyzes the influence of the harmony between traditional and modern music on youth culture. The role of music in shaping the worldview, aesthetic taste, and spiritual education of young people is highlighted, and the importance of promoting national musical heritage through modern methods is revealed. In addition, the role of innovative technologies in the formation of youth musical culture in the context of globalization is discussed.